Age, growth, and sexual maturity of two New Zealand endemic skates, Dipturus nasutus and D. innominatus - Malcolm P. Francis; Caoimhghin Ó Maolagáin; Darren Stevens (New Zealand Journal of Marine and Freshwater Research, 2001)
Rough and smooth skates ( Dipturus nasutus (Banks 1841) and/), innominatus (Garrick & Paul 1974)) were aged by counting growth bands on X‐rays of thick sections of vertebral centra. Band counts were imprecise, but there was no between‐reader bias. Age estimates were not validated. The oldest rough skate was 9 years old, but few were more than 6 years old. Females may live longer than males. The combined sexes von Bertalanffy growth curve was L r = 91.3 (1 ‐ e −0.16 [ t + 1.20 ]). Half the males matured by c. 52 cm pelvic length (PL) and 4 years, and females by 59 cm PL and 6 years. The oldest smooth skate in the sample was 24 years, but longevity probably exceeds that. Females appear to live longer than males. The combined sexes von Bertalanffy growth curve was: L t = 150.5 (1 ‐ e −0.095[ t + 1.06] ). Half the males matured by c. 93 cm PL and 8 years, and females by 112 cm PL and 13 years. Smooth skate are late maturing and long‐lived relative to other skates, whereas rough skate are early maturing with a moderate life span.